FUZZY TIPE-2 MAMDANI UNTUK MENDUKUNG PENGAMBILAN KEPUTUSAN - Humaira (ITP Press, 2014)
The main concept of fuzzy logic is addressing problems that contain uncertainty. Fuzzy System was implemented successly in any field. The first fuzzy is known as type-1 fuzzy. Some time ago, Prof. . Zadeh realize that type-1 fuzzy membership functions is actually a crisp as well . Then in 1975 Prof . Zadeh discovered type- 2 fuzzy logic. However , type- 2 fuzzy logic became popular in early 2000 . According to Jerry Mendel type- 2 fuzzy logic used to model and minimize the effects of uncertainties that may occur on fuzzy logic. The research will analyze one case in DSS (Decision Support System) ie. Selection of supplier for development new product. It is implemented using Mamdani Inference. The result that reduction type with cos (center of sets) method gets I/O surface smoother. Then Interval chanding of Membership Function influence varied recommend decision.